2018
DOI: 10.1002/arch.21448
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of NlHox3, an essential gene for embryonic development in Nilaparvata lugens

Abstract: Hox genes encode transcriptional regulatory proteins that control axial patterning in all bilaterians. The brown planthopper (BPH), Nilaparvata lugens (Hemiptera: Delphacidae), is a destructive insect pest of rice plants in Asian countries. During analysis of the N. lugens transcriptome, we identified a Hox3-like gene (NlHox3) that was highly and specifically expressed in the embryonic stage. We performed functional analysis on the gene to identify its roles in embryonic development and its potential use as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…In this regard, V‐ATPase gene expressed in the midgut of the corn rootworm, Diabrotica virgifera virgifera , has been selected and its RNAi results in mortality high enough to be used in developing a novel insecticide . To have a direct and detrimental effect on insect development, a morphogen (Hox gene) has been targeted by dsRNA, leading to significant embryonic mortality of the brown plant hopper, Nilaparvata lugens . To avoid any adverse effect on mammals, insect‐specific genes such as chitin synthase and ecdysone receptor have been targeted to develop dsRNA insecticide …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, V‐ATPase gene expressed in the midgut of the corn rootworm, Diabrotica virgifera virgifera , has been selected and its RNAi results in mortality high enough to be used in developing a novel insecticide . To have a direct and detrimental effect on insect development, a morphogen (Hox gene) has been targeted by dsRNA, leading to significant embryonic mortality of the brown plant hopper, Nilaparvata lugens . To avoid any adverse effect on mammals, insect‐specific genes such as chitin synthase and ecdysone receptor have been targeted to develop dsRNA insecticide …”
Section: Introductionmentioning
confidence: 99%
“…4 To have a direct and detrimental effect on insect development, a morphogen (Hox gene) has been targeted by dsRNA, leading to significant embryonic mortality of the brown plant hopper, Nilaparvata lugens. 5 To avoid any adverse effect on mammals, insect-specific genes such as chitin synthase and ecdysone receptor have been targeted to develop dsRNA insecticide. [6][7][8] Delivery techniques of efficient dsRNAs to target insects, especially into their cytoplasm, have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Guided by functional analysis, the hub genes in each embryonic stage were identified (Supplementary Figure S3), which laid the foundations for future studies of N. lugens embryonic development. Moreover, previous studies have suggested parental RNAi was a new pest control strategy (Ren et al, 2018) and lasted for seven generations in Sitobion avenae (Abdellatef et al, 2015). Thus, these hub genes in each embryonic stage, combining with parental RNAi, may be used for controlling crop pests such as N. lugens.…”
Section: Discussionmentioning
confidence: 99%
“…Parental RNAi was conducted according to the previously described method (Bucher et al, 2002;Ren et al, 2018). dsRNA synthesis (approximate 250 bp) was carried out following the manipulation with the T7 RiboMAX Express TM RNAi System (Promega, United States).…”
Section: Parental Rnai Embryo Collection and Qrt-pcrmentioning
confidence: 99%
See 1 more Smart Citation